Framework para comércio eletrônico, via internet móvel, mediado por agente de software - Fontes, Diogo Sobral (Universidade Federal de São Carlos, 2002)
The emergent technology of software agents is becoming popular in the last years, due to the increasing of Internet applications. Software Agents were initially used to filter information, find people with similar interests and to automate repetitive processes. Nowadays, they are being used in e-commerce applications, making a revolution in the way of leading the negotiations between people and companies. This technology automates several traditional steps of the purchase and sale process for Internet, reducing the costs and eliminating geographical barriers. This research presents a proposal for the development of an E-Commerce Framework, via Mobile Internet, mediated by Software Agents (FCEMAS). The framework is based on project patterns and Mobile Internet solutions using WAP (Wireless Application Protocol).
Keywords: Internet (Rede de computação); Framework (Programa de computador); Agentes de software inteligentes; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO